2002
DOI: 10.1111/j.1095-8649.2002.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Clove oil as an anaesthetic for adult sockeye salmon: field trials

Abstract: Wild migrating sockeye salmon Oncorhynchus nerka exposed to 20, 50 and 80 mg l 1 of clove oil could be handled within 3 min, recovered within 10 min, and survived 15 min exposure trials. Fish tested at 110 mg l 1 did not recover from 15 min exposure trials. Response curves developed for induction and recovery time considered the following predictors: clove oil concentration, sex, fish length and depth. A significant positive dependence was observed between induction time and fish length for 20, 50 and 80 mg l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(84 citation statements)
references
References 16 publications
8
65
1
4
Order By: Relevance
“…The same study found that Brown Trout (Salmo trutta) and Atlantic Salmon (Salmo salar) of different body sizes did not differ in induction times (as we found for Hyphessobrycon sp.2). Of the few studies that have assessed the relationship between fish size and recovery time, two found no relationship (Hoskonen and Pirhonen, 2004;Prince and Powell, 2000), and one found that larger individuals had quicker recovery times than smaller ones (Woody et al, 2002). This parallels the current results for Hyphessobrycon sp.1 and Hemigrammus sp.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The same study found that Brown Trout (Salmo trutta) and Atlantic Salmon (Salmo salar) of different body sizes did not differ in induction times (as we found for Hyphessobrycon sp.2). Of the few studies that have assessed the relationship between fish size and recovery time, two found no relationship (Hoskonen and Pirhonen, 2004;Prince and Powell, 2000), and one found that larger individuals had quicker recovery times than smaller ones (Woody et al, 2002). This parallels the current results for Hyphessobrycon sp.1 and Hemigrammus sp.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, individuals from Hyphessobrycon sp.1 specie used in treatment D3 are statically lower than treatment D1 and D2. Studies analyzing the effect of standard length on induction and recovery times have reported conflicting results (Prince and Powell, 2000;Walsh and Pease, 2002;Woody et al, 2002;Hoskonen and Pirhonen, 2004;Perdikaris et al, 2010). As with our dissenting results for Hyphessobrycon sp.1 and Hemigrammus sp., larger bodied Whitefish (Coregonus lavaretus) had shorter induction times than smaller ones, while the opposite occurred in Rainbow Trout (Oncorhynchus mykiss) (Hoskonen and Pirhonen, 2004).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Similar observations were made by Grzegorz et al (2006) on Cyprinus carpio L. and Inoue et al (2003) on juveniles of matrinxa Brycon cephalus. Prolonged recovery time with increased anaesthetic dosage has been reported in seven species of tropical reef teleosts (Cunha & Rosa 2006), Oncorhynchus nerka (Woody et al 2002), Rachycentron canadum (Gullian & Villanueva 2009) and Dawkinsia filamentosus (Pramod et al 2010).…”
Section: Discussionmentioning
confidence: 96%